The Importance of the Training-Induced Decrease in Basal Cortisol Concentration in the Improvement in Muscular Performance in Humans. - GRANDYS, M.; MAJERCZAK, J.; KULPA, J.; DUDA, K.; RYCHLIK, U.; ZOLADZ, J. A. (Physiological Research, 2016)
Acute exercise-induced changes in cortisol concentration (C) and training related adaptation within hypothalamic-pituitary-adrenal (HPA) axis has been widely examined, but their influence on muscle strength performance is at best uncertain. Twenty four young healthy men were randomly assigned to an endurance training group (ET, n=12) or to a non-exercising controls (CON, n=12). ET performed supervised endurance training on cycle ergometer for 20 weeks. Endurance training program improved exercise capacity (14 % increase in power output generated at peak oxygen uptake - VO2peak), muscle strength performance (increase in MVC - maximal voluntary contraction - by 9 % and in TTF 50 % MVC - time to fatigue at 50 % MVC - by 21 %) and led to a decrease in basal serum C concentration (P=0.006) and an increase in basal testosterone to cortisol (T/C) and free testosterone to cortisol (fT/C) ratios (P=0.01 and P=0.02, respectively). It was found that the decrease in C concentration (▵ C) was positively correlated to the increase in local muscular endurance (▵ TTF 50 % MVC). No significant hormonal changes were seen in CON group. It is concluded that greater decrease in cortisol concentration after the endurance training is accompanied by poorer improvement in skeletal muscle performance in previously untrained subjects.